Competitive analysis and strategic improvement of polypropylene polytam pf-1000 in indonesia - Rahardi, Naufal; Hartoyo, Hartoyo; Sartono, Bagus (UNIVERSITAS PAKUAN, 2025)
This research intends to assess the competing capabilities of Polytam PF-1000 with other products available in the market Indonesia and suggest alternative approaches to strengthen its market position. A mixed approach was conducted combining survey with 305 respondents and detailed interviews, then using Analytic Hierarchy Process (AHP) method. Multiple regression results suggest that the Demand Conditions variable is the most determinant in competitiveness (β = 0.990, p < 0.05), then Related and Supporting Industries (β = 0.812), Firm Strategy, Structure, and Rivalry (β = 0.218), and lastly Factor Conditions (β = 0.159). It elaborates the necessity of understanding the market, collaboration in the business industry, formulating business strategy, and resource allocation in enhancing competitiveness of Polytam PF-1000. Further AHP (analytical hierarchy process) analysis using 55 stakeholders managed to rank two other group’s components and their weight: Factor Conditions was prioritized and received the most weight at 0.518, followed by Demand Conditions which was rated by 0.261. From the interviews, technological advancement, supply chain improvement, and expansion of market coverage formed the primary strategies. One of the angles of perspective that was surprising is that the consumers want a quicker response to their needs, while the internal stakeholders want investment in the needed resources and infrastructure. Along with regulatory changes and energy efficiency, these are new alternative strategies that were outside Porter’s Diamond.